The Role of Endocrine and Metabolic System in COVID-19 Disease – The Transcampus Experience and Review of Evidence From International Collaborating Groups - Perakakis, Nikolaos; Barthel, Andreas; Bornstein, Stefan R. (Hormone and Metabolic Research, 2022)
The COVID-19 Pandemic has led to a world health crisis with major socioeconomic consequences that have deeply affected our daily lives. Until the end of May 2022, more than 500 million people have been infected by COVID-19 and more than 6 million have died from the disease. Unprecedented efforts in research, illustrated by the more than 250 000 publications in PubMed, have led to the identification of important pathophysiological mechanisms affected by SARS-CoV-2 and have resulted in the development of effective vaccines and treatment protocols for patients with COVID-19.